Local Water Partnership : Universal Model of Water Resources Management - Gryz, Jarosław, (Brill | Wageningen Academic, 2024)
The conservation of water resources together with environment protection will be a challenge for the European Union within the 21st century. Water management nowadays involves the cooperation of farmers, societies, industry and public administra